Pembelajaran Project Based Learning Berdiferensiasi untuk Meningkatkan Keterampilan Kolaborasi dan Hasil Belajar Kognitif Peserta Didik SMA pada Materi Sistem Koloid - Yuli Nestiyarum; Endang Widjajanti (Postgraduate, University of Mataram, 2023)
This research is a Classroom Action Research (CAR) using two cycles, conducted in class XI IPA 1 SMAN 1 Seyegan, Sleman, Yogyakarta which amounted to 36 students. The purpose of CAR is to improve collaboration skills and cognitive learning outcomes of students in class XI IPA 1 at SMA Negeri 1 Seyegan using the Project Based Learning (PjBL) learning model with process and product differentiation. Based on the results of the study, this learning model was able to improve the collaboration skills of students of class XI IPA 1 significantly, namely 17.11%. This learning model is also able to improve the cognitive learning outcomes of students in terms of various aspects, namely the average value, the lowest value, the highest value, the number of students who are complete, and the percentage of classical learning completeness. The average posttest score an increase of 29.38%. Classical learning completeness during the posttest also increased significantly from 22.22% in cycle I to 77.78% in cycle II. This proves that the PjBL learning model with process and product differentiation is able to improve collaboration skills and cognitive learning outcomes of students in class XI IPA 1 at SMAN 1 Seyegan on colloidal system material.